Benzophenone-3 remodels gut microbiota diet-dependently to exacerbate non-alcoholic fatty liver disease in zebrafish - Tao, Junyan; Tian, Linxuan; Yang, Qinyuan; Jiang, Yao; Liu, Yubo; Wang, Junli; Chen, Xiong; Gao, Hui (Frontiers in Microbiology, 2025)
Benzophenone-3 (BP3), a prevalent organic UV filter found in aquatic environments and human tissues, poses potential metabolic risks. This study investigated the combined effects of BP3 (10 μg/L) and a high-fat diet (HFD, 24% crude fat) on non-alcoholic fatty liver disease (NAFLD) development in zebrafish, focusing on gut-liver axis disruption via microbiota. Co-exposure to BP3 and HFD significantly worsened hepatic steatosis, as evidenced by increased triglyceride levels, lipid droplets accumulation, and oxidative damage (elevated hepatic MDA levels and decreased hepatic CAT activity). Additionally, this combined exposure induced gut dysbiosis characterized by a marked decrease in Bacteroidota and Fusobacteriota, along with increased proportions of Proteobacteria and Actinobacteriota, and an altered Firmicutes/Bacteroidota ratio. This dysbiosis compromised intestinal barrier integrity, leading to anterior/middle intestines villus atrophy, endotoxin translocation, and hepatic inflammatory activation. Notably, BP3 demonstrated a diet-dependent effects, depleting Bacteroidia under normal diet while increasing Gammaproteobacteria under HFD. These findings, highlight that BP3 synergizes with HFD to disrupt the microbiota-gut-liver axis, accelerating NAFLD progression, and emphasize the host’s metabolic status as a critical determinant of pollutant-microbiota interactions and toxicity. This diet-dependent effect challenges isolated toxins risk assessments, underscoring the need to incorporate dietary context into NAFLD prevention and environmental health rules.